2004
DOI: 10.1007/s10344-003-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure descriptors regulating the presence of wild rabbit in the National Park of Peneda-Ger�s, Portugal

Abstract: The aim of this work is to assess whether there is a specific structural vegetation pattern for the wild rabbit Oryctolagus cuniculus (L., 1758) that might explain its spatial distribution. The species presence was approached through logistic regression modelling based on selected descriptors of vegetation landscape structure: number of homogeneous vegetation units, their areas and diversity values and heterogeneity indexes. All variables were derived for two hunting areas within the National Park of Peneda-Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In our study, 77% of electrocuted birds were raptors, many of which are sit-and-wait hunters and use mainly forest-crop ecotones (Sánchez-Zapata and Calvo, 1999). Both features are closely linked, given that ecotones are preferred habitats for European rabbits (Oryctolagus cuniculus), the key prey for raptors in the Mediterranean ecosystem (Monzon et al, 2004, Delibes-Mateos et al, 2008, 2009). Presence of prey around pylons is a well-documented predictor of electrocution risk (Tintó et al, 2010;Guil et al, 2011).…”
Section: Bird Electrocution and Landscape Configurationmentioning
confidence: 52%
“…In our study, 77% of electrocuted birds were raptors, many of which are sit-and-wait hunters and use mainly forest-crop ecotones (Sánchez-Zapata and Calvo, 1999). Both features are closely linked, given that ecotones are preferred habitats for European rabbits (Oryctolagus cuniculus), the key prey for raptors in the Mediterranean ecosystem (Monzon et al, 2004, Delibes-Mateos et al, 2008, 2009). Presence of prey around pylons is a well-documented predictor of electrocution risk (Tintó et al, 2010;Guil et al, 2011).…”
Section: Bird Electrocution and Landscape Configurationmentioning
confidence: 52%
“…Our results show, as is the case in the Iberian Peninsula and southern France, that site colonization by the european rabbit has a negative influence on vegetation through the complete absence or much reduced proportion of both the shrub and herb layers (cf. lombardi et al, 2003;monzón et al, 2004;sarmento et al, 2012;Narce et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was been extensively shown that wild rabbit abundance correlates with the amount of ecotone between habitats that provide shelter and habitats that provide food, whilst large homogeneous patches are avoided (Rogers and Myers 1979;Palomares and Delibes 1997;Lombardi et al 2003;Carvalho and Gomes 2003;Monzón et al 2004). Wild rabbits also avoid hard soils where warren building is difficult, whilst their abundance is associated with the available amount of non-irrigated cultures (Angulo 2004).…”
Section: Discussionmentioning
confidence: 97%